Sodobni pristopi v kadrovskem managementu in izobraževanju (University of Maribor Press, 2026)
Contemporary Approaches in Human Resource Management Ano Education. The scientific monograph examines contemporary approaches to human resource management, focusing on sustainable employee management and the digitalization of HR processes. It highlights the challenges of an ageing workforce, absenteeism, employee health, and the work-life balance as key factors for the long-term and successful operation of organizations. Special emphasis is placed on the role of organizational culture, communication, and critical thinking in the era of digitalization and artificial intelligence. At the same tirne, the monograph presents innovative approaches in education, such as the use of artificial intelligence, gamification, and the responsible use of digital media, where artificial intelligence serves as an important support for HR and educational processes rather than a substitute for human judgement.